Crime and Criminal Process Aspects of Secret Surveillance and Recording of Communication in Bosnia and Herzegovina - Kršić, Željko (Kriminalističke teme, 2017)
Reason for writing and research problem(s): Due to the new forms, specific forms of the offenses and the growing technological development and specialization of perpetrators it is difficult to detect and clarify the crimes and provide material evidence. Considering the specialization of perpetrators and more widespread use of modern means of communication in the commission of the crimes it is essential the continuous development of criminology and investigative techniques such as surveillance and recording of communications. Application of these procedures means specific tecniques of forensic science and special criminal tactics in disclosing criminal acts. Aims of the paper (scientific and/or social): The aim is to highlight the need to improve the legal framework for the application of this investigation in a criminal process system in Bosnia and Herzegovina, through comparative legal analysis of the situation in other criminal procedural systems and taking the best solutions in terms of the basis for taking action, duration of action, treatment with the evidence, and more. Methodology/Design: For the purpose of this study a survey was conducted by processing of statistical data, which shows that this special investigative action is the most commonly used special investigative action in Bosnia and Herzegovina. The work will show comparative legal analysis of the legal provisions that regulate the way of implementation of this action in Bosnia and Herzegovina and some countries in the region, including some states of the European Union. Research/Paper limitation: The survey was conducted in the territory of BiH and the survey covered the period from 01.01.2012. until 31.12.2016. year. The paper also presents comparable legal solutions. Results/Findings/General Conclusion: Surveillance and recording of communications is a specific special investigative action, which profoundly affects the privacy of citizens, and which now has greater and wider use, and requires constant analysis of the existing legal provisions, court practice, their improvement and development and training of criminal investigation techniques and tactical procedures. Research/Paper Validity: In the last fifteen years in the criminal procedural legislation of Bosnia and Herzegovina and neighboring countries, as one of the special investigative actions is included, in different modalities, also secretly monitoring and recording communications. The results of the research and the comparative legal analysis of legal solutions can serve to improve the current legal in BiH.